4D Printing: Enabling Technology for Microrobotics Applications. (18th January 2021) - Adam, Georges; Benouhiba, Amine; Rabenorosoa, Kanty; Clévy, Cédric; Cappelleri, David J.
Abstract : This review demonstrates that 4D printing constitutes a key technology to enable significant advances in microrobotics. Unlike traditional microfabrication techniques, 4D printing provides higher versatility, more sophisticated designs, and a wide range of sensing and actuation possibilities, opening wide new avenues for the next generation of microrobots. It brings disruptive solutions in terms of variety of stimuli, workspaces, motion complexities, response time, function execution, and genuinely 3D microrobots. This review brings to light how soft and smart materials directly printed in 3D are particularly well suited for microrobotics requirements. This review gives an overview of 4D printing in microrobotics, highlighting advanced microrobotics requirements, fabrication methods, used smart materials, activation techniques, recent advances in the microrobotics field, and emerging opportunities. Abstract : Herein, Georges Adam and co‐workers present a comprehensive review of 4D printing technologies specifically targeted for microrobotic applications. It provides a background on 4D printing techniques, active materials used, activation techniques, and how they all can be used in the context of creating a new generation of smart microrobots.